VIOLATION OF CALCIUM-PHOSPHORUS METABOLISM IN CHILDREN OF A PATIENT WITH CHRONIC PYELONEPHRITIS (LITERATURE REVIEW) - Shodiya Sh. Shadieva; Lobar Y. Kamolova (Central Asian Journal of Medicine, 2023)
The state of the organism is formed by various factors of the internal and external environment, among which the state of calcium-phosphorus metabolism occupies an important place. Violation of the structure and function of the organs involved in the regulation of phosphorus-calcium metabolism is the cause of various diseases that develop during the life of the child. The kidneys are the main organ in the regulation of phosphorus-calcium homeostasis in both physiological and pathological conditions.